Chinese Economic Success - Inspiration for Economy, Policy and Security - Ondrusek, Milos (Communications - Scientific Letters of the University of Zilina, 2011)
This paper focuses on the recent changes in global economic relations and increase of China's importance in global politics, security and economy. It describes the changes in China's security, economic, political strategy and its influence to its own development and empowering its position in international economic, political and security relations. The implications for the EU security management are described, too.
Keywords: China; economic security; sustainable development; soft power; strategic investments; Africa